Pelestarian Kawasan Masjid Raya Baiturrahman Banda Aceh melalui Pendekatan Lanskap Budaya - Fatrialis Zahrul Akbar Syafri; Muhammad Qardawi; Algifari Maruza; Ria Maulida; Cut Alisa Sisilia; Zya Dyena Meutia (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The Baiturrahman Grand Mosque area in Banda Aceh is one of the most important cultural landscapes in Aceh, combining historical, religious, architectural, and social values. As an ancient mosque with strong ties to the identity of the Acehnese people, preservation of this area cannot be done solely on the building aspect, but must encompass all elements of the cultural landscape such as outdoor spaces, vegetation, circulation patterns, and social and religious practices. This study aims to analyze the elements of the cultural landscape that shape the Banda Aceh Grand Mosque area and formulate a comprehensive preservation approach.